Escala de avaliação das práticas parentais : controlo e aceitação - Gaspar, Tânia (2018)
The aim of the study was proposing and validate the Parenting Practices Assessment Scale. Parenting practices play an important role in children positive development, subjective wellbeing and global mental health. Measure parenting practices it is an important contribute to deeply understand this concept and its relation with children development. Was involved a sample of 2256 parents of 2256 children from 5th grade (48.8%) and 7th grade (51.2%), mean age 11.58 years old; SD 1.41; ranging from10–16 (48,4% between 10 and 11 years of age and 51,6% 12 years or older); there were 46,2 % boys and 53.8 % girls. Through Principal Component Analyses were found two dimensions, one related to control and another linked to acceptance. Results related to psychometric properties showed adequate values. Additionally, items discriminating validity and concurrent validity were inspected with measures related to subjective wellbeing and dimensions of subjective wellbeing. This instrument seems to be adequate for the measurement Parenting Practices, and can be useful in several contexts, such as health psychology and family interventions.